An integrative literature review and critical reflection of intersectionality theory. Issue 4 (21st June 2021) - Ruiz, Ashley M.; Luebke, Jeneile; Klein, Katie; Moore, Kaylen; Gonzalez, Michael; Dressel, Anne; Mkandawire‐Valhmu, Lucy
Abstract: Intersectionality theory has been used by nursing scholars to offer insight into how multiple systems of oppression mutually interact to impact health and to examine how multiple social modes of existence shape individual and group experiences of health inequality. The application of intersectionality theory, however, requires a reflexive critical lens to more effectively inform nursing science and practice. We draw on a comprehensive integrative literature review to offer a critical reflection by considering the semantic and structural consistency, generalizability, simplicity and complexity, and the utility and value of intersectionality theory to nursing science and practice. If nurses are to effectively utilize intersectionality theory, it is essential that we are able to analyze and speak to the multiple modes of existence based on historical, social, economic, and political processes that impact the health of those we serve. Critical examination of intersectionality enables nurses to further consider its value and usefulness when applied to nursing science and practice, particularly when addressing health and social inequalities.